IMPLEMENTATION OF COMMUNITY-BASED ENVIRONMENTAL CARE CHARACTER IN ELEMENTARY SCHOOL STUDENTS - Retnasari, Lisa; Indriyani, Ika Nur (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2024)
The current environmental equilibrium requires global and national solutions. This study aims to evaluate the implementation of community-based environmental character care in Umbulharjo State SD 2, as well as its supportive and inhibitory factors. This research uses a type of descriptive research qualitative approach. The research subjects consisted of the head of the school, parents, CFP accompanying, teachers, and students of class VI A at the Umbulharjo State SD 2. Data collection on the study was done through observations, interviews, and documentation. The validity of the data in this study uses source triangulation and triangulation techniques. The data is then analyzed using a data analysis model according to Miles and Huberman that includes data collection, data reduction, data presentation, and conclusion and verification. The results of this study show that the implementation of community-based environmental caring character in pupils in Umbulharjo State SD 2 was realized through the collaboration of parents and OISCA. Collaboration is carried out through community-based character-enhancing education implementation measures that include: 1) Identification and analysis of school needs; 2) Identifying community participation; 3) building networks and collaboration; 4) designing character enhancement educational activities; 5) Program implementation; 6) Program evaluation; and 7) Maintaining the sustainability of collaboration. Factors supporting the collaboration include the availability of extensive land, the enthusiasm of school citizens, and the presence of support from partners. Implementation of community-based environmental caring character in Umbulharjo State SD 2 through collaboration between parents, OISCA, and schools, highlights the importance of active participation of the community in addressing environmental gaps at the local level.